2006
DOI: 10.1063/1.2227707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surfactants Sb and Bi on the incorporation of zinc and carbon in III/V materials grown by organometallic vapor-phase epitaxy

Abstract: The incorporation of both dopants and background impurities during the organometallic vapor phase epitaxial ͑OMVPE͒ growth of GaAs, GaInP, and GaP has been significantly altered by the use of the surfactants Sb and Bi. Sb and Bi are isoelectronic with the group V host elements, and so produce no independent doping. This paper demonstrates that the incorporation of Zn can be increased by an order of magnitude in GaP to a value of approximately 10 20 cm −3 , the highest value reported to date. Additionally, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 27 publications
2
29
2
Order By: Relevance
“…Hydrogen also plays a role in the doping process [253]. When Sb is incorporated into the growth process, both H and Zn concentrations increase [253]. The physical mechanism of surfactant-enhanced doping remained unclear at that time.…”
Section: Surfactant-enhanced Dopingmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrogen also plays a role in the doping process [253]. When Sb is incorporated into the growth process, both H and Zn concentrations increase [253]. The physical mechanism of surfactant-enhanced doping remained unclear at that time.…”
Section: Surfactant-enhanced Dopingmentioning
confidence: 99%
“…Experimentally, it was found that Sb can enhance the incorporation of Zn into InGaP and GaP [248,253]. Howard et al used Sb and bismuth (Bi) as surfactants to enhance the incorporation of Zn into InGaP during the OMVPE growth [253].…”
Section: Surfactant-enhanced Dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether small elements like hydrogen can serve as surfactants is an interesting and open question in the growth of GaN or ZnO [39,40,[44][45][46]. Limited studies of H as surfactants were reported in a few other semiconductors.…”
Section: Introductionmentioning
confidence: 99%